2023
DOI: 10.3390/ijms24010819
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionization Degree of Poly(amidoamine) Dendrimer and 5-Fluorouracil on the Efficiency of Complex Formation—A Theoretical and Experimental Approach

Abstract: Due to their unique structure, poly(amidoamine) (PAMAM) dendrimers can bind active ingredients in two ways: inside the structure or on their surface. The location of drug molecules significantly impacts the kinetics of active substance release and the mechanism of internalization into the cell. This study focuses on the effect of the protonation degree of the G4PAMAM dendrimer and the anticancer drug 5-fluorouracil (5FU) on the efficiency of complex formation. The most favorable conditions for constructing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The efficiency of DOX binding to the G4.0 PAMAM dendrimer strongly depends on the degree of ionization of the components, as in the case of 5-fluorouracil [ 35 , 36 ]. The highest efficiency occurs at pH 9.0 and 9.5, where DOX concentrations are 21 and 19 ppm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficiency of DOX binding to the G4.0 PAMAM dendrimer strongly depends on the degree of ionization of the components, as in the case of 5-fluorouracil [ 35 , 36 ]. The highest efficiency occurs at pH 9.0 and 9.5, where DOX concentrations are 21 and 19 ppm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This may be related to the tendency of DOX to aggregate strongly at high concentrations [ 28 , 37 ]. Previous studies assessed the effectiveness of forming the G4PAMAM complex with 5-fluorouracil (G4-5FU) [ 35 , 36 ]. These studies have shown that a dendrimer molecule binds around 20 5FU molecules, and the binding efficiency strongly depends on the degree of ionization of both components [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that a shoulder peak appears at 288.8 eV in the C 1s core level spectrum of 5-FU loaded CH 2 Cl-graphene, corresponding to the carbon atoms involved in C-F bonds. 56 In the Cl 2p highresolution XPS spectra of CH 2 Cl-graphene and 5-FU loaded CH 2 Cl-graphene (Fig. 7(b)), two peaks are located at 200.04 eV and 202.63 eV, which can be ascribed to Cl 2p 1/2 and Cl 2p 3/2 , respectively.…”
Section: Structural and Morphological Characteristicsmentioning
confidence: 97%
“…They have also been widely employed as co-delivery systems for the simultaneous administration of genes and drugs [ 11 , 12 , 13 ]. Hydrophobic drugs with different mechanisms of action and low solubility can be physically encapsulated or entrapped inside PAMAM dendrimers’ cavities or pockets [ 14 , 15 , 16 , 17 , 18 , 19 ]. This molecular encapsulation is responsible for the increased solubility in water and controlled release profile.…”
Section: Introductionmentioning
confidence: 99%